Strategies for ventilation in acute, severe lung injury after combat trauma. Issue 1 (12th November 2013) - Brogden, Thomas G; Bunin, J; Kwon, H; Lundy, J; McD Johnston, A; Bowley, DM
Abstract : Post-traumatic Acute Respiratory Distress Syndrome (ARDS) continues to be a major critical care challenge with a high associated mortality and extensive morbidity for those who survive. This paper explores the evolution in recognition and management of this condition and makes some recommendations for treatment of post-combat ARDS for military practitioners. It is aimed at the generalist in disciplines other than critical care, but will also be of interest to intensivists.